Factors that influence the consumer choices of Islamic bank for banking products and services in Segamat, Johor / Fatin Nur Farihah Ghazali - Ghazali, Fatin Nur Farihah (2017)
The aim of this study was to identify the factors that influence consumer choices of Islamic banks for banking products and services among the banking consumers in Segamat, Johor. Islamic banking in Malaysia continually growth and there are still arise of confusion among potential consumer of Islamic bank who may observe that Islamic banks in reality are no different as conventional banks. So, this research is carried out to identify the factors that influence consumer choice in Segamat area. In addition, this study also provides result of whether the variables such as convenience, service quality, security, technology and Islamic branding have significant effect on consumer choice of Islamic banks. The research is done through distributing questionnaires to respondents while the target population is the consumers of Islamic banks in Segamat, Johor. Statistical Package for Social Science (SPSS) version 22.0 was used to analyse the data which collected from the survey. Respondent's feedback was analysed and presented through the test of Reliability Test, Pearson Correlation Analysis and Multiple Regression Analysis. The research finding showed that convenience, service quality, security and technology have significant relationship between the consumer choices of Islamic banking in Segamat, Johor. However, results for the Islamic branding have insignificant relationship with the consumer choices of Islamic banking in Segamat, Johor. As conclusion, this results have met the objective of determining the relationship of factors influencing the consumer choices of Islamic bank in Segamat, Johor.